Perancangan Alat Distribusi Ikan Segar Menggunakan Media Pendingin Ice Pack untuk Pedagang Ikan Keliling - Nyoman Dhira Prayasa; I Wayan Widia; I Made Anom S. Wijaya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2019)
Research on fresh fish distribution tool using ice pack as cooling media for small-scale fresh fish retailer was conducted. The research aimed to design fresh fish distribution system for small- scale fresh fish retailer which can maintain the quality of fresh fish during transportation. This research was carried out through several stages, i.e. identification of needs, functional design, structural design and performance test. Fresh fish distribution tool using ice pack as cooling media for fresh fish small - scale retailer consisted fish storage room, fish storage room cover, ice pack, rack and fish storage stand. Performance test was carried out by observing the room temperature of fish storage room in unloaded condition and fish temperature during 4 hours transportation, determining the coefficient of performance (COP) value and observing the fish quality during trans portation with organoleptic test. The result showed that the room temperature of fish storage room in unloaded condition could reach-12.3 0C after 24minutes operation and maintain temperature with 5 0C upper limit for 14,3 hours, the distribution toolusing ice pack as cooling media could maintain the fish temperature with 5 0C upper limit for 32.03 hours and organoleptic quality values before transportation, after transportation and after 12 hour storage were 8.0, 7.4, and 6.2. Values of COP was 0.67. This result has fulfilled the requirement of fish quality standard according to national standardization institution.